Research on the Path to Realize the Functions of Academic Student society in Chinese Universities - Deng, Cong; Tang, Songlin (Journal of Roi Kaensarn Academi, 2023)
This study is to explore the influencing factors of their innovation behavior. Based on this argument and relevant literature, three basic potential variables of the model are constructed, namely: the motivation of club members to participate in activities, the innovation atmosphere of club organizations, and the innovation behavior of club members. There are four hypotheses in total, To build a "theoretical model for the realization of innovative functionality of academic Student society in Chinese universities". Data was collected through online questionnaires, and statistical tests were conducted using SPSS22.0 and AMOS24.0 software. The statistical tests included descriptive statistical analysis, reliability and validity testing of test items, model fitting testing, research hypothesis testing, and mediation effect testing. The results show that: (1) the participation motivation of the members of academic Student society in Chinese universities has a positive impact on the innovative behavior of the members of the associations; (2) the organizational innovation climate of academic Student society in Chinese universities has a positive impact on the participation motivation of the members of academic Student society in Chinese universities; (3) the participation motivation of the members of academic Student society in Chinese universities has a positive impact on the innovative behavior of the members of the associations; (4) The participation motivation of the members of academic Student society in Chinese universities plays a mediating role between the participation motivation of the members of academic Student society in Chinese universities and the innovative behavior of the members of the associations; Finally, based on the research findings, several corresponding research suggestions were proposed.